Nano design to smart gels - Bacani, Rebeca; Trindade, Fabiane; Politi, Mario Jose; Triboni, Eduardo Rezende (Micro & nano technologies., 2019)
Nano Design for Smart Gels addresses the formation and application of technological gels and how nanostructural prospects are fundamental to gelling. Topics focus on the classification of gels based on small molecules and polymer gellers, biogels, stimulation conditions, topological, thermodynamic and kinetic aspects and characterization techniques. The book outlines structure and characterization concepts in order to provide pragmatic tools for the design and tailoring of new functional gel architectures. It provides an important source for readers and researchers who are currently or may soon be in research with gels, presenting an overview of fundamental topics.